Protocol for the Perfusion and Angiography Imaging Sub-Study of the Third International Stroke Trial (IST-3) of Alteplase Treatment within Six-Hours of Acute Ischemic Stroke. Issue 6 (August 2015) - Wardlaw, Joanna M.; von Kummer, Rudiger; Carpenter, Trevor; Parsons, Mark; Lindley, Richard I.; Cohen, Geoff; Murray, Veronica; Kobayashi, Adam; Peeters, Andre; Chappell, Francesca; Sandercock, Peter A. G.
Rationale: Intravenous thrombolysis with recombinant tissue Plasminogen Activator improves outcomes in patients treated early after stroke but at the risk of causing intracranial hemorrhage. Restricting recombinant tissue Plasminogen Activator use to patients with evidence of still salvageable tissue, or with definite arterial occlusion, might help reduce risk, increase benefit and identify patients for treatment at late time windows. Aims: To determine if perfusion or angiographic imaging with computed tomography or magnetic resonance help identify patients who are more likely to benefit from recombinant tissue Plasminogen Activator in the context of a large multicenter randomized trial of recombinant tissue Plasminogen Activator given within six-hours of onset of acute ischemic stroke, the Third International Stroke Trial. Design: Third International Stroke Trial is a prospective multicenter randomized controlled trial testing recombinant tissue Plasminogen Activator (0·9 mg/kg, maximum dose 90 mg) started up to six-hours after onset of acute ischemic stroke, in patients with no clear indication for or contraindication to recombinant tissue Plasminogen Activator. Brain imaging (computed tomography or magnetic resonance) was mandatory pre-randomization to exclude hemorrhage. Scans were read centrally, blinded to treatment and clinical information. In centers where perfusion and/or angiography imaging were used routinely in stroke, these images were also collected centrally, processed and assessed using validated visual scores and computational measures. Study outcomes: The primary outcome in Third International Stroke Trial is alive and independent (Oxford Handicap Score 0–2) at 6 months; secondary outcomes are symptomatic and fatal intracranial hemorrhage, early and late death. The perfusion and angiography study additionally will examine interactions between recombinant tissue Plasminogen Activator and clinical outcomes, infarct growth and recanalization in the presence or absence of perfusion lesions and/or arterial occlusion at presentation. The study is registered ISRCTN25765518.